PENGARUH PERENCANAAN PAJAK DAN INSENTIF NON PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Sutrisno, Mohamad; Sari, Inayah Adi; Astuti, Yanti Puji (PERMANA, 2018)
The Effect of Tax Planning and Non-Tax Incentives toward Earnings Management at Manufacturing Companies listed on Indonesia Stock Exchange 2013-2017. Thesis, Tegal: Faculty of Economics, Pancasakti University Tegal. 2018. The purpose of this study is to examine the effect of tax planning and non-tax incentives simultaneously and partially toward earnings management at manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. This research is descriptive research with quantitative approach. The sample used is automotive sub-sector manufacturing companies and components listed in Indonesia Stock Exchange period 2013-2017. The number of companies sampled this research there are 45 companies by using purposive sampling method. While the data analysis method used is descriptive statistical test, classical assumption test, multiple linear regression analysis, simultaneous significance test (F test), test of individual parameter significance (T test) and coefficient of determination. Based on the results of research indicate that tax planning and non-tax incentive simultaneously have a significant effect toward earnings management with significance value 0,000. While partially tax planning, earnings pressure and firm size have significant effect to earnings management with value of significance respectively 0,037,0,000 and 0,049. As well as leverage and earnings bath partially no effect toward earnings management with a significance value of 0.436 and 0.146 respectively. Keywords : Tax planning, earnings pressure, leverage, earnings bath, company size, earnings management